Structured Literature Analysis on Sustainability Report Disclosure in Public Sector Organizations - Arifai, Muhammad; Mariana, Mariana; Fahlevi, Heru; Indriani, Mirna; Darwanis, Darwanis (Universitas Mercu Buana, 2025)
Objectives: This study examines the adoption of sustainability reporting in Public Sector Organizations (PSOs), focusing on (1) stakeholder expectations, (2) implementation challenges, and (3) the impact on accountability and value creation. It also identifies existing gaps in sustainability reporting frameworks and provides strategic recommendations to enhance transparency and effectiveness in public sector sustainability disclosures.Methodology: A Structured Literature Review (SLR) was conducted on 97 articles from Scopus (1990–2024), selected using keywords such as